How is the effect of Multiple Intelligences on Students’ Self-Confidence and English Daily Exam Scores? - Aftarini, Tari; Syahri, Indawan; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2023)
The research aims to understand the impact of multiple intelligences toward students. Confidence and daily exam score of English Subject. This research was carried out at SMP Negeri 2 Abab, Penukal Abab Lematang Ilir Regency. This research used a quantitative approach. Data testing techniques were used in this research. 193 students were given a multiple intelligences test to find out what is their dominant intelligence and then used the data testing techniques to find out whether there was an impact or not toward the students’ confidence and daily exam score in English Subjects. The result of this research showed that (1) the student’s dominant intelligence did not significantly affect the English daily exam score. (2) some of the students’ dominant intelligence affected the students’ confidence in learning the English process, they were verbal intelligence, kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, and naturalistic intelligence. So, it can be concluded that the students’ dominant intelligence didn’t have any impact on the student’s exam scores while some of the students’ dominant intelligence had an impact to the student’s self-confidence.